THE POLITICAL POWER OF THE MEDIEVAL ECCLESIASTICAL AUTHORITIES AND THE MAMLUK-ILKHANATE WARFARE BETWEEN 1284 AND 1304: COMPARATIVE STUDY OF THE ARMENIAN APOSTOLIC CHURCH AND THE ASSYRIAN APOSTOLIC CHURCH IN CILICIAN ARMENIA AND ILKHANATE - Saduakassov, Aidar (Nazarbayev University School of Sciences and Humanities, 2021)
The modern history often avoids researching the marginalized medieval Christian religious institutions due to the lack of their political significance. However, the medieval accounts present the information about their significant role in the Mongol conquest of the Mamluk Sultanate. From the one hand, the study of the ecclesiastical representatives of the Assyrian Apostolic Church in the Mongol court is one of the underexplored topics in the medieval history of Central Asia and Middle East. Morgan and Grousset explored the significance of the Nestorian authorities in the court as a matter of the personal favorability of khans, however, the effect of the Mongol conquest to the power of Christians in Ilkhanate was undefined. Russell tried to examine this connection; however, her paradigm lacks scientific proofs and proper methods of analysis. On the other hand, the studies of the Armenian Apostolic Church were better developed. Ghazarian analyzed the effects of the Latin-Armenian encounters to the Armenian domestic politics. Dashdonbog explored how the Mongol Armenian relationships affected the institutional power of the Armenian Church. However, the authors fail to examine the question of why the Armenian Church became one of the most significant religious entity among marginalized Christian religions in the Middle East. This comparative study explores the relationships between the Mamluk-Ilkhanate warfare during 1284 and 1304 and the political power of the Nestorian and Armenian clergies in Ilkhanate and Cilician Armenia. The main argument is that the political power of the Nestorian and Armenian ecclesiastical authorities was damaged by the Mongol-Mamluk warfare between 1284 and 1304. In particular, apart the military damages of the warfare, the consequences of Islamization of ilkhans and reciprocity with Catholics became significant factors that explain the downward trend in political power of the Christian clergies in Cilician Armenia and Ilkhanate. Mainly, these factors were the intentional discourses to stimulate the military capabilities of the Armenians and Mongols through the attraction of the domestic and foreign alliances against Mamluks. Furthermore, the study will also prove that the political ties between Armenian kings and ecclesiastical authorities affected the survival of the Armenian Church and localization of the Nestorian clergy. Hereby, the institutional power, political positions in the courts, patronage and social status as well as repressions and institutional devastations are the main variables that determine the political power of the ecclesiastical authorities in Ilkhanate and Cilician Armenia. The thesis mainly explores the periods of Lewon II and Hetum II reigns in Cilician Armenia; and simultaneously evaluates the period from Arghun khan’s reign to Ghazan khan’s rule in Ilkhanate. The study uses content and linguistic-political discourse analyses as major methodological tools. The research is based on Syriac, Latin, Armenian and Persian primary sources that were conducted between 13th and 16th centuries. In particular, the diplomatic reports, correspondences between rulers, ecclesiastical and Islamic chronicles will be evaluated throughout the study. Hopefully, this paper will contribute to the political, military and religious history of the medieval Middle East, Ciscaucasia and Central Asia
Keywords: Type of access: Open Access; Mamluk Sultanate; Assyrian Apostolic Church; Mongol court; Cilician Armenia; Ilkhanate